Role of brain glycogen in the response to hypoxia and in susceptibility to epilepsy - López-Ramos, Juan C.; Duran, Jordi; Gruart, Agnès; Guinovart, Joan J.; Delgado-García, José M. (Frontiers in Cellular Neuroscience, 2015)
Although glycogen is the only carbohydrate reserve of the brain, its overall contribution to brain functions remains unclear. It has been proposed that glycogen participates in the preservation of such functions during hypoxia. Several reports also describe a relationship between brain glycogen and susceptibility to epilepsy. To address these issues, we used our brain-specific Glycogen Synthase knockout (GYS1Nestin-KO) mouse to study the functional consequences of glycogen depletion in the brain under hypoxic conditions and susceptibility to epilepsy. GYS1Nestin-KO mice presented significantly different power spectra of hippocampal local field potentials (LFPs) than controls under hypoxic conditions. In addition, they showed greater excitability than controls for paired-pulse facilitation evoked at the hippocampal CA3-CA1 synapse during experimentally induced hypoxia, thereby suggesting a compensatory switch to presynaptic mechanisms. Furthermore, GYS1Nestin-KO mice showed greater susceptibility to hippocampal seizures and myoclonus following the administration of kainate and/or a brief train stimulation of Schaffer collaterals. We conclude that brain glycogen could play a protective role both in hypoxic situations and in the prevention of brain seizures.